A short form of the Speech, Spatial and Qualities of Hearing scale suitable for clinical use: The SSQ12. (June 2013) - Noble, William; Jensen, Niels Søgaard; Naylor, Graham; Bhullar, Navjot; Akeroyd, Michael A.
Abstract Objective: To develop and evaluate a 12-item version of the Speech, Spatial and Qualities of Hearing scale for use in clinical research and rehabilitation settings, and provide a formula for converting scores between the full (SSQ49) and abbreviated (SSQ12) versions. Design: Items were selected independently at the three centres (Eriksholm Research Centre, MRC Institute of Hearing Research, University of New England) to be representative of the complete scale. A consensus was achieved after discussion. Study sample: The data set (n = 1220) used for a factor analysis (Akeroyd et al, submitted) was re-analysed to compare original SSQ scores (SSQ49) with scores on the short version (SSQ12). Results: A scatter-plot of SSQ12 scores against SSQ49 scores showed that SSQ12 score was about 0.6 of a scale point lower than the SSQ49 (0–10 scale) in the re-analysis of the Akeroyd et al data. SSQ12 scores lay on a slightly steeper slope than scores on the SSQ49. Conclusions: The SSQ12 provides similar results to SSQ49 in a large clinical research sample. The slightly lower average SSQ12 score and the slightly steeper slope reflect the composition of this short form relative to the SSQ49.